Pepper Novel Serine-Threonine Kinase CaDIK1 Regulates Drought Tolerance via Modulating ABA Sensitivity - Lim, Junsub; Lim, Chae Woo; Lee, Sung Chul (Frontiers in Plant Science, 2020)
Adaptation to drought stress is essential for plant growth and development. Plants often adapt to water deficit conditions by activating the ABA signaling. Here, we report that the pepper CaDIK1 (Capsicum annuum Drought Induced Kinase 1) gene is essential for plant tolerance to drought stress. CaDIK1 contains a serine-threonine kinase domain, which plays a role for attachment of phosphate to the target protein. The expression levels of CaDIK1 are upregulated in pepper leaves by ABA, drought, NaCl and H2O2 treatments suggesting its role in abiotic stress response. We used CaDIK1-silenced pepper and CaDIK1-overexpressing (OX) transgenic Arabidopsis plants to evaluate their responses to ABA and drought. CaDIK1-silenced pepper plants conferred a reduced ABA sensitivity and drought hypersensitivity, which was accompanied by high levels of transpirational water loss. CaDIK1-OX plants displayed opposite phenotypes to CaDIK1-silenced peppers. In contrast, substitution of Lys350 to Asn in the kinase domain of CaDIK1 did not lead to alteration of drought sensitivity. Collectively, these data indicate that CaDIK1 is a positive regulator of the ABA-mediated drought-stress tolerance.